2021
DOI: 10.3390/molecules26247654
|View full text |Cite
|
Sign up to set email alerts
|

Current Photoactive Molecules for Targeted Therapy of Triple-Negative Breast Cancer

Abstract: Cancer is the second leading cause of death worldwide; therefore, there is an urgent need to find safe and effective therapies. Triple-negative breast cancer (TNBC) is diagnosed in ca. 15–20% of BC and is extremely aggressive resulting in reduced survival rate, which is mainly due to the low therapeutic efficacy of available treatments. Photodynamic therapy (PDT) is an interesting therapeutic approach in the treatment of cancer; the photosensitizers with good absorption in the therapeutic window, combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…PDT is an alternative therapeutic methodology that utilizes a photosensitizer (PS), a suitable excitation light source, and oxygen molecules for treatment [ 215 ]. It was begun in the mid-1900s, and Dougherty and his co-workers developed its modernized expression in1975.…”
Section: Ongoing Treatments For Triple-negative Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…PDT is an alternative therapeutic methodology that utilizes a photosensitizer (PS), a suitable excitation light source, and oxygen molecules for treatment [ 215 ]. It was begun in the mid-1900s, and Dougherty and his co-workers developed its modernized expression in1975.…”
Section: Ongoing Treatments For Triple-negative Breast Cancermentioning
confidence: 99%
“…Basically, a specific wavelength is energized PS that shifts its vitality to the molecular oxygen, consequently producing responsive oxygen species (ROS), for example, hydrogen peroxide (H 2 O 2 ), singlet oxygen ( 1 O 2 ), hydroxyl free radical (OH•) and superoxide ions (O 2 ¯ • ) can oxidize macromolecules and prompting tumor cell removal. However, conventional PS has a limited therapeutic effect due to this reason the other excitation illumination sources have been explored, such as chemiluminescence (chemiluminescent emitter transfer light energy to the PS), Cerenkov radiation (charged particles produced electromagnetic radiation when passed through dielectric medium, resulting triggering local polarization), and X-rays (transposition of X-rays by energy transducer to optical fluoresces for PDT and radiotherapy) [ 215 ].…”
Section: Ongoing Treatments For Triple-negative Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that about 0.16 million patients were affected by BC in the United States in 2017 ( Torre et al, 2016 ; Li et al, 2020a ). Since 2020, there have been 2.3 million new cases of BC worldwide every year, and the total number of BC patients is predicted to increase by 50% by 2040 ( Dias et al, 2021 ; Shao and Varamini, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main treatments for breast cancer are surgery [2], chemotherapy [3], radiation therapy [4], hormone therapy [5], and targeted therapy that uses drugs to target specific genes [6] and proteins [7] that are involved in the growth and survival of breast cancer cells. In recent years, photodynamic therapy (PDT) has been an interesting therapeutic approach in the treatment of cancer [8]. Currently, published studies show that PDT in combination with chemotherapy has become an available cancer treatment which uses functionalized organic nanoparticles (NPs) for effective PDT treatment of breast cancer [9].…”
Section: Introductionmentioning
confidence: 99%